Common issues and organizational behaviors in the prevention and control of major diseases - Jiaoyan LI; Huinan HAN; Xiaoyu WANG; Jing LIANG; Fang WANG; Beizhu YE; Zhihong ZHANG; Xiao GAO; Yun WEN; Yuan LIANG (Editorial Office of Chinese Journal of Public Health, 2024)
Due to the common characteristics of major communicable and non-communicable chronic diseases targeted by major disease prevention and control measures - such as variability and ambiguity - both face common challenges in the implementation of group strategy. Additionally, these strategies must be conducted within the units/institutions/communities where people work, study, and live, focusing on groups rather than individuals, thus inherently involving organizational behavior. This paper proposes addressing the common issues of group prevention and control of major diseases from the perspective of organizational behavior, leveraging collective power through organizational roles. Moreover, based on relevant studies, it preliminarily introduces four organizational behavior elements aimed at addressing these common issues and analyzes the interrelationships among these four elements.